Pengembangan Media Pembelajaran Sejarah Kebudayaan Islam Kelas XI Menggunakan Aplikasi Canva - Sari, Kartika; Ma’arif, Iin Baroroh (YASIN, 2025)
The lack of student enthusiasm for learning at MA Al-Bairuny is attributed to a monotonous teaching process, in which teachers predominantly rely on the lecture method. This approach leads to boredom and disengagement, necessitating the integration of information technology-based innovations to enhance student involvement. This study aims to develop instructional videos using the Canva application to improve content comprehension and promote more effective learning. The research adopts a Research and Development (R&D) approach utilizing the ADDIE model (Analyze, Design, Development, Implementation, Evaluation), involving 30 eleventh-grade students. Data were collected through observation, interviews, documentation, and questionnaires. Media expert validation yielded a score of 74%, material expert validation 81%, and student responses 79.83%, indicating that the media is considered engaging. These findings confirm that Canva-based media is suitable for teaching Sejarah Kebudayaan Islam and can enhance students’ motivation and interest in learning. The study implies that technology-based instructional media can serve as an effective alternative to address low learning motivation in the classroom.